Perlindungan Hukum Terhadap Anak Yang Terlibat Kejahatan Terorisme - Zafania Helsa Siahaya; Juanrico Alfaromona Sumarezs Titahelu; Denny Latumaerissa (TATOHI: Jurnal Ilmu Hukum, 2023)
Introduction: Laws and regulations regarding terrorism, in practice there are still those who commit criminal acts of terrorism in Indonesia by attacking vital objects and public facilities.Purposes of the Research: The research aims to examine and discuss the forms of legal protection given to children who are involved in terrorism crimes and to examine and explain the mechanism of legal protection for children who are involved in terrorism crimes. Methods of the Research: The research method used is normative juridical with descriptive analytical research type, the technique of collecting legal materials by conducting library research on legal materials, namely primary legal materials and secondary legal materials. The technique of analyzing legal materials is obtained from a qualitative classification.Results of the Research: The results of this study indicate that the legal protection given to children involved in terrorism crimes includes guaranteeing and protecting children's rights, such as the right to live, grow, develop and participate optimally in accordance with human dignity and protection from violence and discrimination. And the Juvenile Criminal Justice System sees that the handling of children involved in terrorism crimes can be carried out with mechanisms such as an approach that purely prioritizes child welfare and an approach to legal intervention. The specificity of the juvenile justice process with the concept of restorative justice.